Implementation of the laboratory strategic framework to strengthen health laboratory services in Eastern Mediterranean Region, 2016–2023 - Fausta S. Mosha; Rana Hajjeh; Rachel Ochola; Amany Ghoniem; Yvan J.F. Hutin (African Journal of Laboratory Medicine)
Background: Laboratories and diagnostics services are critical to universal health coverage and public health response. We assessed the extent of the implementation and functionality of the 2016–2023 Eastern Mediterranean Region (EMR) laboratory strategic framework.